Formation of personal and team skills among students of humanities during swimming lessons - Grigan S.A. ,; Verina T.P. ,; Mikhailyuk N.V. ,; Korchagin P.P. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to substantiate the use of swimming facilities for the development of personal and social qualities of students in an educational environment. Methods and structure of the study. The purpose of the scientificresearchconductedat the DonStateTechnicalUniversityduringonesemesterwas to determine the degree of influence of regularswimmingtrainingon the development of keypersonalqualitiessuchas self-discipline,responsibility,teamworkandsociability.Thestudyinvolved60students of the Faculty of Humanities, who made up an experimentalgroup that regularlyattendedswimmingclasses. Results and conclusions. Research has shown that swimming promotes the development of personal qualities of students of humanities and improves their interaction skills. Systematic training increases self-confidence and a sense of responsibility, both for one's own actions and for the well-being of the group. The example of self-discipline demonstrated by the participants motivates other students to take a more responsible attitude towards their studies. Group classes strengthen team spirit, a sense of belonging and mutual understanding between students.